Cryoprotective Efficiency of Some Cryoprotectants Depending on Cooling Rate - Chernobai, N. A.; Gurina, T. M.; Pakhomov, A. V. (Problems of Cryobiology and Cryomedicine, 2024)
The survival of testes interstitial cells after freeze-thawing using the cooling rates of 1; 5 and 10 deg/min and glycerol (7%), dimethyl sulfoxide (10%), ethylene glycol (7%) and dimethyl formamide (5%) solutions has been estimated. Using of glycerol provided sufficiently high (up to 75%) cell survival under all the studied cooling rates. Cell survival increased (from 56% upto 83%) if cooling rates were elevated from 1 up to 10 deg/min in the case of other cryoprotectants. Cooling rates about 10 deg/min provided sufficiently high level of post-thaw cell survival.